The big country [videorecording (DVD)] - Peck, Gregory, 1916-2003; Simmons, Jean, 1929-2010; Baker, Carroll, 1931-; Heston, Charlton; Ives, Burl, 1909-1995; Hamilton, Donald, 1916-2006 (Western legends., 2001)
A retired ship captain moves west to marry and start life over as a rancher. He finds himself between two families at war over cattle watering rights, unaccepted by the local people, and in a deteriorating relationship.